African financial development dynamics: big time convergence. Issue 2 (1st July 2014) - A. Asongu, Simplice
Abstract : Purpose: – Assessment of African financial development dynamic convergences in money, credit, efficiency and size. The paper aims to discuss these issues. Design/methodology/approach: – The empirical evidence is premised on 11 homogenous panels based on regions (Sub-Saharan and North Africa), income-levels (low, middle, lower-middle and upper-middle), legal-origins (English common-law and French civil-law) and religious dominations (Christianity and Islam). The paper examines convergence in financial intermediary dynamics of depth, efficiency, activity and size. Findings: – Findings suggest that countries with small-sized financial intermediary depth, efficiency, activity and size are catching-up countries with large-sized financial intermediary depth, efficiency, activity and size, respectively. The paper also provide the speeds of convergence and time necessary to achieve a full (100 percent) convergence. Practical implications: – The presence of strong links among African banking sectors may present little opportunity for portfolio diversification. The convergence patterns show positive steps toward regional integration. As a policy implication, African governments should not relent in structural and institutional reforms. Originality/value: – It is the first critical assessment of convergence in financial intermediary development dynamics in the African continent.